2017
DOI: 10.3389/fpls.2017.00351
|View full text |Cite
|
Sign up to set email alerts
|

Study of Commercially Available Lobelia chinensis Products Using Bar-HRM Technology

Abstract: There is an unmet need for herbal medicine identification using a fast, sensitive, and easy-to-use method that does not require complex infrastructure and well-trained technicians. For instance, the detection of adulterants in Lobelia chinensis herbal product has been challenging, since current detection technologies are not effective due to their own limits. High Resolution Melting (HRM) has emerged as a powerful new technology for clinical diagnosis, research in the food industry and in plant molecular biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This might represent a potential health risk for consumers ( Geck et al, 2020 ). DNA barcoding and high-resolution melting have been used to distinguish the classification of an unknown plant sample ( Kress et al, 2005 ; Pang et al, 2013 ; Sun et al, 2017 ). These techniques should be implemented in the Mexican pharmacopeia to guarantee the quality and safety of herbal products sold in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…This might represent a potential health risk for consumers ( Geck et al, 2020 ). DNA barcoding and high-resolution melting have been used to distinguish the classification of an unknown plant sample ( Kress et al, 2005 ; Pang et al, 2013 ; Sun et al, 2017 ). These techniques should be implemented in the Mexican pharmacopeia to guarantee the quality and safety of herbal products sold in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the prior characterization of the target plant group through DNA barcoding studies is a prerequisite. Hitherto, several studies have reported its potential application in different plant species ( Ganopoulos et al, 2012 ; Kalivas et al, 2014 ; Schmiderer et al, 2015 ; Song et al, 2016 ; Sun et al, 2016 , 2017 ; Meistertzheim et al, 2017 ; Mishra et al, 2017 ). S. alexandrina is well known for its laxative properties and high export value as a bulk herb in trade from India.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced molecular techniques enable researchers to use DNA to analyze samples of many different origins. To date techniques such as amplified fragment length polymorphism ( Shaw et al, 2009 ), sequence characterized amplified regions ( Theerakulpisut et al, 2008 ; Kiran et al, 2010 ), DNA barcoding ( Chen S. et al, 2010 ; Pang et al, 2013 ), loop-mediated isothermal amplification ( Li et al, 2016b ; Zhao et al, 2016 ), and high resolution melting (HRM) ( Li et al, 2016a ; Osathanunkul et al, 2016 ; Sun et al, 2017 ) have been widely used to identify medicinal plants. Of these techniques, DNA barcoding offers fast, sensitive, and accurate identification of plant species in a wide variety of herbal products.…”
Section: Introductionmentioning
confidence: 99%